The Spatial Correlation Between Green High-Quality Development and Technology Finance - Jiang, Lili; Wang, Hui; Wang, Shaowen; Hu, Zhifei; Tong, Aihua; Wang, Yifeng (Frontiers in Environmental Science, 2022)
Based on an analysis of the function of technology finance for green high-quality development, this paper selects 35 basic indicators from the five dimensions of innovation, coordination, greenness, openness, and sharing to construct an Green High-quality Development Index. Moreover, 14 basic indicators are selected from the three dimensions of technology finance resources level, technology finance input level, and technology finance output level to construct a technology finance development evaluation system. Then, using the entropy method, panel data from the period 2000-2020 from China’s 30 provinces was employed to assess the Economic Quality Development Index and the Technology Finance Development Index. The results show that provinces and cities with a good economic development level have a relatively high level of strong economic and technology finance development, including Beijing, Shanghai, and Jiangsu. Moreover, the results reveal a certain gap between different provinces. Multiple regression, static panel regression, dynamic panel regression, the static space Dubin model, the dynamic space Dubin model, and the semi-parametric space lag model were used to test the effect of technology finance on China’s green high-quality development . This study found that technology finance has significantly enhanced green high-quality development of China's as a whole through a non-linear promotion effect. To better promote green high-quality development , the following measures are recommended: (1) improving the level of technological and financial development, (2) increasing the scale of government expenditures, (3) strengthening infrastructure construction, (4) accelerating the construction of new urbanization, and (5) improving the level of human capital.